The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1469-7580.1998.19220257.x
|View full text |Cite
|
Sign up to set email alerts
|

The organisation of the enteric nervous system in the submucous and mucous layers of the small intestine of the pig studied by VIP and neurofilament protein immunohistochemistry

Abstract: The arrangement of the enteric ganglia and nerve fibre plexuses was examined in the submucous and mucous layers and around Peyer's patches of the porcine small intestine to clarify their organisation. Immunohistochemistry of vasoactive intestinal peptide (VIP) and neurofilament proteins in wholemounts, chopped or paraffin sections was used to locate the neural elements. The ganglia of the internal and external submucous plexuses were situated at 2 different topographic locations, being clearly demarcat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 14 publications
8
44
0
2
Order By: Relevance
“…Besides studies in rat (Bridges et al 1986;Mestres et al 1992), cattle and pig (Balemba et al 1998(Balemba et al , 1999, the interest on human mucosal neurons derived mainly from clinical and pathohistological background (Lassmann 1975;Hirschowitz and Rode 1991;Fang et al 1993;Tunru-Dinh and Wu 2007). These investigators evaluated sections stained with classical histological or histochemical methods and found that the presence of mucosal neurons in human intestines is variable.…”
Section: Introductionmentioning
confidence: 98%
“…Besides studies in rat (Bridges et al 1986;Mestres et al 1992), cattle and pig (Balemba et al 1998(Balemba et al , 1999, the interest on human mucosal neurons derived mainly from clinical and pathohistological background (Lassmann 1975;Hirschowitz and Rode 1991;Fang et al 1993;Tunru-Dinh and Wu 2007). These investigators evaluated sections stained with classical histological or histochemical methods and found that the presence of mucosal neurons in human intestines is variable.…”
Section: Introductionmentioning
confidence: 98%
“…The porcine small intestine contains three major ganglionated plexuses: a myenteric plexus and two submucosal plexuses; the submucosal plexus is further subdivided into the internal submucosal plexus (ISP) and external submucosal plexus (ESP; Timmermans et al 1990;Balemba et al 1998). The porcine ISP is structurally less complex than the myenteric plexus or ESP (Timmermans et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These neurons have been also found to contain neuropeptides (Schultzeberg et al 1980;Korman et al 1989;Vittoria et al 1992;Bredkjaer et al 1994;Balemba et al 1998) and the NADPH-d enzyme (Fang et al 1993). Neverthless, mucosal ganglia and single neurons are considered to be ectopic from the submucous plexus (Stöhr 1934;Lassmann 1975) and the mucous plexus to be aganglionic (Schultzeberg et al 1980;Costa et al 1987;Timmermans et al 1990;Burns Fig.…”
Section: Discussionmentioning
confidence: 93%